2019
DOI: 10.1155/2019/1251536
|View full text |Cite
|
Sign up to set email alerts
|

Depth-Dependent Cellular Response from Dental Bulk-Fill Resins in Human Dental Pulp Stem Cells

Abstract: The proper choice of dental composite resins is necessary based on the minimal cytotoxicity and antiodontogenesis on human dental pulp stem cells for dental pulp-dentin tissue repair and regeneration. The aim of this study was to evaluate the cytotoxicity and antidifferentiation effects of dental bulk-fill resins, able to be polymerized as a bulk status for filling deep cavity of a tooth by single light curing, against human dental pulp stem cells (hDPSCs) from three compartments corresponding to depth (0-2, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In a similar study on the toxicity of fluid and paste bulkfill composite resins conducted on L929 mouse fibroblasts by Demirel et al [29] it was reported that at the end of 72 h composite extracts caused a statistically significant decrease in cell viability level, which is in line with the former. In a study on human pulp cells, by examining the toxic effect of bulkfill composite samples in terms of whether it change at the layers of different polymerization depths [0-2, 2-4 and 4-6 mm] Lee et al [30] stated that as the irradiation depth increased the more toxicity occurred, and the highest cytotoxicity was observed in the layer of 4-6 mm depth. However, Nascimento et al [31] reported that bulk-fill resins exhibited low level and/or no cytotoxicity on L929 cells, except for Opus, which showed more moderate cytotoxicity, as pointed out in the MTT assay index.…”
Section: Resultsmentioning
confidence: 99%
“…In a similar study on the toxicity of fluid and paste bulkfill composite resins conducted on L929 mouse fibroblasts by Demirel et al [29] it was reported that at the end of 72 h composite extracts caused a statistically significant decrease in cell viability level, which is in line with the former. In a study on human pulp cells, by examining the toxic effect of bulkfill composite samples in terms of whether it change at the layers of different polymerization depths [0-2, 2-4 and 4-6 mm] Lee et al [30] stated that as the irradiation depth increased the more toxicity occurred, and the highest cytotoxicity was observed in the layer of 4-6 mm depth. However, Nascimento et al [31] reported that bulk-fill resins exhibited low level and/or no cytotoxicity on L929 cells, except for Opus, which showed more moderate cytotoxicity, as pointed out in the MTT assay index.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the thickness of dentin is closely related to the diffusion of substances to the pulp through the dentinal tubules [ 49 ]. It is important to note that in bulk-fill composite resins, greater irradiation depth results in greater cytotoxicity, particularly in increments greater than 4 mm [ 50 ]. This may be associated with our results, as we applied a 4 mm thickness in all experimental tests.…”
Section: Discussionmentioning
confidence: 99%
“…Asdada et al 50 evaluated the cytotoxicity and antidifferentiation effects of bulk fill composites against human dental pulp stem cells (hDPSCs) in three compartments corresponding to the depth (0-2, 2-4 and 4-6 mm) from the light source region and found that the cytotoxic effect increased with increasing depth. In order to protect the ability of dental pulp stem cells to survive and differentiate, they said that care should be taken when choosing bulk-fill resins, especially when fixing deep cavities.…”
Section: Cytotoxicity Studies On Resin-containing Materialsmentioning
confidence: 99%